PERTUMBUHAN INKLUSIF DI PROVINSI SULAWESI SELATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Azwar Azwar (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2016)
The purpose of this research was to measure and analyze the inclusiveness of economic growth in south sulawesi and its determinants on 2011-2014 period. Using the annualy data from Badan Pusat Statistik (BPS) and Direktorat Jenderal Perimbangan Keuangan (DJPK), this research applies Social Mobility Curve Model by Anand et al (2013), poverty-equivalent Growth Rate (PEGR) model by Kasen (2010)and panel regression with fixed Effect Model (CEM) to measure and analyze the inclusiveness of economic growth and its determinant. The empirical result show that the economic growth in eastern Indonesia is not fully inclusive in agregat It can be seen from Equity Income Index (w0 indicated that the economic growth not pro poor yet. From determinant analysis, healthy index and local government expenditure partially have positive effect on index of inclusive growth. The others such as economic growth, unemployment, education and number of poor people have negative effect howewer.